Vaccination and Pandemic Control in Bangladesh: Post Vaccination COVID-19 Positive Cases among Health Care Providers - Halim, Kazi Shafiqul; Saha, Suchisree; Parvin, Sayda Tanjina; Afroz, Sharmin; Roy, Sajib; Sanwar, Tasnim; Mitul, Md Mahmudul Hasan; Ahmed, Nusrat; Shakila, Afsana Zerin; Saha, Puspita; et al. (Bangladesh Medical Journal, 2024)
Vaccination was started on a trial basis in Bangladesh from 27th January, 2021 and started mass vaccination from 7th February, 2021. Since starting of mass vaccination it was noticed that, the health care providers (HCPs) who received two doses of Astra-Zeneca were then reported of being infected. This cross-sectional study was conducted during the period of July to December 2021 and data were collected from July to August 2021. The main objective was to measure the proportion of post vaccinated Corona Virus Disease-19 (COVID-19) positive cases among healthcare providers working in different healthcare facilities in Bangladesh and aimed to collect available evidence to characterize these infections and correlations with different co-morbidities. This study was carried out among 450 vaccinated HCPs who received 2 doses of vaccine at various health care facilities (HCFs) from 32 districts of Bangladesh. Data were collected from HCPs (Doctors, Nurses, Lab technician) who willing to participate irrespective of age and sex. Among the HCPs nearly three-fourth (71.6%) was doctors, 21.3% nurses and 7.1% were lab technologists. Here, most of the (88.0%) respondents were in age group 21 to 40 years and other 22.0% was in age group 41 to 59 years. The number of Male-female respondents was equal and 77.8% of the respondents was Muslim followed by Hinduism (20.2%), Buddhist and Christian 2.0%. Study finds that 27.6% of the respondents was post vaccination COVID-19 positive (PVC-19+) (according to their rt-PCR test result). Less than one-fifth (18.7%) of the respondents had pre-existing co-morbidities among them 8.2% was suffering from hypertension (HTN), 6.0% asthma, 4% Diabetes Mellitus (DM), 2.0% Obesity, 1.1% ischemic heart disease (IHD) and 1.1% was others co-morbidities. Among the PVC-19+ cases most of them (84.6%) were in age group 21-40 years, male-female ratio was 1:0.9 and 81.5% was Muslim. More than three-fourth (77.4%) of positive cases were doctors, 17.7% nurses and 4.8% was lab technicians; among the PVC-19+ cases 87.9% was symptomatic. Three-fourth (75%) of the positive cases had fever, 51.6% had lost of smell and taste, 49.2% showed fatigue/ or malaise, 48.4% dry cough, 43.5% headache, 26.6% runny nose, 25.8% felt muscle pain, 19.4% sore throat, 18.5% shortness of breathing, 14.5% experienced joint pain, 9.7% had productive cough and 32.3% complained for other symptoms and signs. Majority of the PVC+19+ cases (57.26%) developed complications; among them 71.8% had tiredness/ fatigue, 31% difficulty in thinking/ concentrating, 21.1% headache, 19.7% cough, 15.5% dizziness, 14.1% loss of smell or taste, 12.7% joint or muscle pain, 12.7% fast-beating or pounding heart, 11.3% shortness of breathing, 8.5% chest pain and 29.9% developed other complications. Pre-existing co-morbidity was found in 66.94% of positive cases, among those 41.5% HTN, 36.6% asthma, 14.6% DM, 14.6% obesity, 4.9% IHD and 9.8% had others co-morbidity. Chi-square test for independence with α = 0.05 was done to assess association, hypertension (P = 0.009) and asthma (P = 0.001) with PVC-19+ cases was statistically significant. Hypertensive and asthmatic HCPs are more likely to be COVID-19 positive even after complete vaccination. Healthcare providers are at high risk for contracting COVID-19 and might become infected at home or nosocomially while caring for patients or interacting with other staff members. COVID-19 vaccination together with incessant use of personal protective equipment (PPE) might be recommended for HCPs to combat its pandemicity. Bangladesh Med J. 2022 Sept; 51(3): 1-9